Paralomis White, 1856 (Crustacea: Decapoda: Anomura) from India, with morphological variability in Paralomis indica Alcock & Anderson, 1899 - Tiwari, Shivam; Padate, Vinay P.; Venugopalan, Vishnu K.; Cubelio, Sherine Sonia; Takeda, Masatsune (Zootaxa, 2022)
Deep-water king crabs of the genus Paralomis White, 1856 collected during three cruises of the Fishery Oceanographic Research Vessel Sagar Sampada in the western Bay of Bengal (528–777 m depths), one cruise in the eastern Bay of Bengal off Great Nicobar Island (337 m depth), and four cruises in the southeastern Arabian Sea (315–1245 m) were identified. They are referred to Paralomis ceres Macpherson, 1989, recorded for the first time from Indian waters and P. indica Alcock & Anderson, 1899, reported for the first time from the Bay of Bengal and the Andaman Sea. In addition, this study reports the morphological variability among the P. indica populations in the shape of the carapace and dorsal rostral spines, nature of the branchial and cardiac regions and abdominal marginal spines, and the relative lengths of pereopods 2–4. Mitochondrial Cytochrome oxidase I (594 base pairs) and 16S rRNA (503 bp) gene sequences of P. ceres and P. indica (602 and 497 bp, respectively) revealed that they formed distinct lineages. A key to the Indian Ocean species of Paralomis is provided.